An Urban Thermal Vulnerability Mapping for Climate Mitigation: A Case from a Coastal Megacity in Saudi Arabia - Maghrabi, Ahmad (Journal of King Abdulaziz University: Environmental Design Sciences, 2024)
Rapid urban expansion is considerably affecting urban surface properties through the substitution of natural landscapes with impervious surface areas. These alterations considerably affect the thermal properties of urban landscapes and increase urban heat island (UHI) intensity and thermal vulnerability; therefore, mapping the thermal vulnerability to mitigate public health concerns is essential. In this study, we mapped the thermal vulnerability of the Jeddah megacity in Saudi Arabia by using principal component analysis (PCA) and a fuzzy analytical hierarchy process (fuzzy-AHP) model. We also conducted correlation and regression anal-yses to understand the relationships and impacts of the remote-sensing indices on thermal vulnerability. The results showed that from 2000 to 2020, built-up land, water bodies, and open land increased by approxi-mately 50%, 4.46%, and 14.11%, respectively. We found that the south-eastern parts of the city were highly vulnerable according to the thermal vulnerability map. In both models, 73.64% (PCA-based model) and 57.29% (fuzzy-AHP-based model) of the city were characterized as thermally vulnerable zones. In our correlation results, we showed that ecological parameters, such as the normalized difference vegetation (NDVI) and moisture indices (NDMI), as well as wetness, had negative correlations with urban thermal vulnerability, while the correlations for land surface temperature (LST) and the urban thermal field variance index (UTFVI) were positive. Thus, in this study, we constructed an effective framework for climate mitigation strategies that can be used to reduce urban thermal or heat vulnerability.